Universal and Language-Specific Patterns in the Acquisition of Verb Argument Structures in German. Issue 2 (2nd April 2016) - Leischner, Franziska N.; Weissenborn, Jürgen; Naigles, Letitia R.
ABSTRACT: The study investigated the influence of universal and language-specific morpho-syntactic properties (i.e., flexible word order, case) on the acquisition of verb argument structures in German compared with English. To this end, 65 three- to nine-year-old German learning children and adults were asked to act out grammatical ( The sheep goes .) and ungrammatical (* The sheep goes the horse .) sentences. Similar to English, German speakers changed the verb meaning depending on the number of sentence NPs which was more evident in younger than older participants. However, the effect was generally smaller in German than in English. This result indicates that learners of case marked languages as German rely less on the number of sentence NPs when learning and interpreting verb argument structures. Much more relevant seems to be the case marking cue for learners of these languages.